Effects of thyme powder and aqueous extract on fatty acid profile of breast meat in broiler chicks - Belali, Majid (Array, 2021)
This experiment was performed to evaluate the effects of thyme (Thymus vulgaris) extract and thyme powder on fatty acid profile of breast meat in broilers. Experimental treatments included aqueous extract of thyme (50 and 100 mg/kg feed) and thyme powder (150 and 250 mg/kg feed) which were used in combination with the basal diet (control). The obtained results revealed the highest percentage of unsaturated fatty acids was related to the higher levels of thyme powder and thyme extract; the highest mean was related to thyme extract (100)+thyme powder (250), and the lowest to thyme extract (0)+thyme powder (0). In general, in the present study, it can be concluded that the use of thyme powder and thyme extract in the diet of Ross 308 broilers decreased some saturated fatty acids and increased unsaturated fatty acids which have health benefits.